EFEKTIVITAS PELAKSANAAN BLENDED LEARNING DI SMAN 4 SINGARAJA - I Wayan Redhana; I Nyoman Suardana (Universitas Negeri Surabaya, 2021)
The purpose of this Community Partnership Program was to describe the effectiveness of the implementation of blended learning at SMAN Singaraja, Buleleng, Bali. For that, five subjects were used as pilots for the implementation of blended learning projects. They were Chemistry, Physics, Biology, English and Religion. The selection of them as pilot projects was based on the readiness of subject matter partners to carry out blended learning and partners competencies in mastering information technology. Before implementing the blended learning, the partners created online contents of the subjects. During the creation of these online contents, the partners were guided by Community Partnership Program implementers. The platform used to create online content was google classroom. The implementation of blended learning used the flipped classroom model. In this model, students learnt the contents first at home uploaded online by partners. The contents uploaded online in the forms of learning materials, textbooks, learning videos, students worksheets, and assignments related to the topic being studied. The results of implementation of the blended learning were as follows. The average score of partners' skills in implementing the blended learning were 2.72 and 4.38, respectively, with a normalized gain score of 0.73 (relatively high). Students learning outcomes had reached the classical learning completeness of 87.50% (exceeding the classical completeness criteria of 85%). Students responded to the implementation of blended learning very well (the average score of 4.35).